Prediction of pituitary stalk position in pituitary adenomas by visualization of the hypothalamo-hypophyseal tract using diffusion tensor imaging tractography. Issue 10 (March 2018) - Wang, Fuyu; Zhang, Jiashu; Wang, Peng; Zhou, Tao; Meng, Xianghui; Jiang, Jinli
Abstract : Abstract: The preservation of pituitary stalk during surgery is very important for neurosurgeons. Sometimes, it is hard to identify the pituitary stalk in the operation. The hypothalamo-hypophyseal tract (HHT) projects through the pituitary stalk to the posterior pituitary gland. If the HHT can be identified, the position of pituitary stalk will be visualized. The diffusion tensor imaging (DTI) fiber tracking technique has been widely used for the quantitative assessment of the white matter integrity and thus may be suitable for the evaluation of the HHT. DTI was used to track the HHT in 11 patients with pituitary adenoma, and the location of the tract was compared with the pituitary stalk of postoperative image in those patients. The fiber tracking and 3D visualization of the HHT were successfully carried out in all 11 patients. Comparison between the tract and pituitary stalk of postoperative magnetic resonance imaging (MRI) was carried out in 9 patients. The results revealed that the position of tract was consistent with the pituitary stalk of postoperative MRI image in 8 patients (88.9%). The properties of tract showed that the median number of tract was 5.18 ± 7.00, the median fractional anisotropy (FA) was 0.14 ± 0.04, and the median length was 28.81 ± 7.94 mm. HHT can be tracked and visualized with the DTI-FT technique. It will be helpful to identify the location of pituitary stalk preoperatively.